Auditory attentional load modulates the temporal dynamics of audiovisual integration in older adults: An ERPs study - Yang, Weiping; Li, Shengnan; Guo, Ao; Li, Zimo; Yang, Xiangfu; Ren, Yanna; Yang, Jiajia; Wu, Jinglong; Zhang, Zhilin (Frontiers in Aging Neuroscience, 2022)
As older adults experienced degenerations in perceptual ability, it is important to gain from the audiovisual integration. Due to attending one and more auditory stimuli while performing another task is a common challenge for older adults in everyday life. Therefore, it is necessary to probe the effects of auditory attentional load on the audiovisual integration in older adults. The present study used event-related potentials (ERPs) and a cross-modal divided attention paradigm (Go-Nogo task + rapid serial auditory presentation (RSAP) to investigate the temporal dynamics of audiovisual integration. Behavioral results showed that both older and younger adults responded faster and higher accuracy to audiovisual stimulus than that of visual and auditory stimulus present alone. ERPs revealed a weaker audiovisual integration under no attentional auditory load condition at the earlier processing stages, and, conversely, stronger in the late stages. Moreover, audiovisual integration was greater in older adults than in younger adults at the time intervals 60-90ms, 430-530ms and 140-210ms. Notably, only under the low load condition in the time interval of 140-210ms, we found audiovisual integration of older adults being significantly greater than that for the younger adults. These results delineate the temporal dynamics of the interacts with auditory attentional load and audiovisual integration in aging, suggested that modulation of auditory attentional on the audiovisual integration and enhanced audiovisual integration in older adults.